Halal Message Design “No Pork, No Lard” on Consumer Purchasing Deci-sions at All You Can Eat Wangja Korean Barbeque Restaurant - Ferdian, Ilham; Rina, Nofha (Indonesian Journal of Social Science Research, 2024)
Nowadays, the public in this nation is becoming more knowledgeable about eating halal meals due to increasing the uses of social media as a medium to get information. Usually, Muslim consumers will select restaurants that have halal certificate, especially for All You Can Eat restaurant. But in order to attract more consumers, some restaurants that do not have a halal certificate will advertise their restaurant with “No Pork, No Lard” signage. The aim of this study is to determine the effect of the halal message design “No Pork, No Lard” on consumer purchasing decisions. A quantitative methodology used in this research and a questionnaire was used to collect the data. The research results show that the halal message design "No Pork, No Lard" has a significant effect on Wangja Korean Barbeque consumer purchasing decisions by 50%.